THE CORRELATION BETWEEN THE SECOND YEAR STUDENTS’ FOREIGN LANGUAGE ANXIETY OF ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU AND THEIR SPEAKING ABILITY - Khotimah, Khusnul; Eliwarti, Eliwarti; Novitri, Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The objective of this research is to find out if there is any significant correlation between the second year students’ foreign language anxiety of English Study Program of Universitas Riau and their speaking ability. This is a correlational research with two variables. In conducting this research, 40 students were selected to be the sample using convenience sampling technique. The instrument used to collect the data was a questionnaire adapted from the FLCAS (Foreign Language Classroom Anxiety Scale designed by Horwitz et al, 1986). There were two kinds of data used in this study i.e. primary data which are the students’ questionnaire responses and secondary data which are their speaking III scores taken from the third semester of 2016/2017 academic year. The calculation of the students’ questionnaire responses resulted in a mean of 3,14, indicating a moderate level of anxiety. The correlation between the students’ foreign language anxiety and their speaking ability were measured using Pearson Product Moment method using SPSS (Statistical Package for Social Sciences) version 23. The data analysis shows that the correlation coefficient value is -.339 and the correlation is significant at the 0.05 level (2-tailed) which means that there is a significant, low negative correlation between students’ foreign language anxiety and their speaking ability. This shows that a student’s speaking ability which is indicated by his/her speaking score tends to decrease as the increase of his/her anxiety level.Key Words: Correlation, Foreign Language Anxiety, Speaking Ability